Critical description of handwritten music manuscripts and materials of Jimmy Boyle - Lee, Sze May (2017)
In response to the recovery of a set of materials left by the iconic composer of Malaysia the late Jimmy Boyle in 2014 that contains many handwritten manuscripts of his unpublished works, songbooks, field notes and open reel recordings, this study is conceived to provide an academic documentation of the said materials. The objective of this study is therefore to examine the set of music materials recovered by Jimmy Boyle, and to provide a critical description on what the materials contain, provide, indicate and imply as a historical source from the viewpoint of composer study. In locating the study within a broader frame of music and identity, the discourse on a multiple “self” by various sociologists such as Schrage, Levinas and Spivak was utilized to construct the multiple images of Boyle as an all rounded music person. The two main components in the research design are the creation of a catalogue of archive for the recovered materials, and the writing of critical description on different aspects of Boyle based on the themes emerged from the manuscript analysis. Analysis of the basic structure of Boyle’s composition, as well as a cross-item comparison was conducted. The result of the study consists of firstly a complete Catalogue of Archive for Jimmy Boyle’s Personal Work of Music 2017 that covers 193 item. The thematic description on Jimmy Boyle reveals that love songs is one major portion of Boyle’s songwriting career. Evidence of jazz related materials portrays an image of Boyle as an all rounded jazzman that was intuitive and inventive and was filled with great sense of humor. Description on “cultural tunes” reveals Boyle’s unending interest with the music culture of the “others”, in which he imitates, studies as well as making effort to disseminate music cultures of various ethic group in the region to wider audience. Future research can expand their foci onto the discourse of local composers’ individual creativity and intertextuality in the post-colonial music history.